From Silenced Victims To National Heroines : Acts Of Impersonation In Narratives Of Le Ly Hayslip And Nora Okja Keller - Chow, Sheat Fun (2012)
This study focuses on the narratives of Le Ly Hayslip and Nora Okja Keller as they explore traumatic events that resulted from transnational histories; the Vietnam War (1959-1975) and the Japanese occupation of Korea during World War II in which the issue of comfort women emerged. Through Hayslip’s autobiographies When Heaven and Earth Changed Places and Child of War, Woman of Peace and Keller’s novel, Comfort Woman, the meaning of women’s sexuality and its interaction with issues of memory, nation and nationalism are explored as thematic anchors. As Asian American women’s national loyalty is often determined through their sexual alliances, their sexuality and identities are active sites of contestation and revision. As a result of conflicting definitions regarding their multiple identities, Asian American women’s narratives reveal the negotiation of multiple affiliations. Various subversive strategies as forms of resistance are often employed in their narratives to re-negotiate the positions and identities of their female protagonists as national subjects and not merely sexual objects or victims. Drawing on memory, autobiographical, deconstruction and feminist studies, this study shows how Hayslip and Keller employ “acts of impersonation” as subversive strategies in their writings to counter racist and sexist construction of Asian American women’s identities. Their writings are performative acts that reveal the negotiations of multiple affiliations and challenge the notions of “authenticity” and “truths” associated with productions of memory.